Perawatan Fuel Oil Purifier Guna Pengoptimalan Bahan Bakar di Atas Kapal MV. Lumoso Karunia IX - Mohamad Afdlin Ardiyanshah; Kriswanto Kriswanto (Politeknik Pelayaran Sulawesi Utara, 2024)
Purification or separation is important in the performance of the purifier to be able to avoid problems that occur in the boat engine. Therefore, it is necessary to carry out maintenance through fuel cleaning to have good fuel quality. The purifier itself functions to clean fuel from liquid and solid impurities (sludge) which can cause damage to the engine due to the use of unclean fuel. The methods used are namely the descriptive qualitative method. If you want to get quality fuel, it is necessary to select the appropriate gravity disc, measure the temperature of the fuel before purification, and ensure that the bowl is in a normal state and finally maintain the bowl regularly